Use of Animated Video Learning Media to Increase Learning Interest - Irmayu, Aida; Caska, Caska; Gimin, Gimin (FKIP - Universitas Riau, 2024)
Lack of student interest in learning can be a problem because it will affect the quality and results of learning. One solution that can be done to overcome low student interest in learning is by using animated video learning media. The purpose of this study was to determine the effect of animated video learning media on student interest in learning. This research data is pre-test and post-test data conducted at SMA Negeri 1 Bukit Batu. Using quantitative research with experimental methods. The results of hypothesis testing conducted with the N-Gain score obtained results 0.7648> 0.7 which means the effectiveness is high. For N-Gain Percent the average value obtained is 76.4811> 76 which means effective. It is concluded that the use of animated videos can effectively increase students' interest in learning.